ANALISIS RIMA DALAM MANTRA PADA KESENIAN KUDA LUMPING DI DESA TANAH ABANG KECAMATAN PAMENANG KABUPATEN MERANGIN - Neni Wulansari; Abdoel Gafar (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research was based on the desire to preserve the art of Kuda Lumping in Tanah Abang Village, Pamenang District, Merangin Regency, which contains rhythmic mantras. The rhythm heard from the mantra can be viewed from the aspect of rhyme in the mantra. This study aims to describe the use of rhyme in the art mantra in Tanah Abang Village. The research method used is a descriptive research method with a qualitative approach. This study describes the use of types of rhyme in the mantra. The data for this study are in the form of rhymes found in the kuda lumping art mantras in Tanah Abang Village. The data for this study were obtained from five informants called pawang. The results of this study obtained a description of five types of rhyme in the kuda lumping art mantra in Tanah Abang Village. “Silang” rhymes were found as many as six, “berpeluk” rhymes were found as many as six, rangkai rhymes were found as many as four, ‘kembar” rhymes were found as many as six, and “patah” rhymes were found as many as seven. Of the twenty-nine rhyme findings in this mantra, the most widely used rhyme is “patah” rhyme. Keywords: mantra, rhyme, Kuda Lumping